High-resolution multibeam bathymetry of the northern Mid-Atlantic Ridge at 45–46° N: the Moytirra hydrothermal field - Somoza, Luis (2022)
This work presents a new high-resolution multibeam bathymetric map of a segment of active deep sea-floor spreading in the Atlantic Ocean, the northern Mid-Atlantic Ridge (MAR) at 45–46º N. New high-resolution bathymetry data were acquired using an Atlas multibeam echosounder onboard the research vessel Sarmiento de Gamboa during the EXPLOSEA-2 survey in 2019. The final map of the MAR (50 m cell grid size) at the original scale of 1:200,000 shows a segment of 140 × 35 km of the MAR, at water depths from 715 to 3700 m. This new high-resolution bathymetric map allows to better defining the submarine morphology of the Moytirra hydrothermal active field, the only high-temperature field identified between the Azores Archipelago (Portugal) and Iceland. ROV submarine observations reaching the deepest part of the system for the first time show giant anhydrite-sulfide chimneys up to 20 m high, active strong black smokers and polymetallic massive sulfides.